2001
DOI: 10.1037/h0087147
|View full text |Cite
|
Sign up to set email alerts
|

White fears and native apprehensions: An integrated threat theory approach to intergroup attitudes.

Abstract: Motivational and cognitive factors have been used to explain negative attitudes toward out-group members. According to the integrated threat theory of prejudice, negative intergroup attitudes are predicted by proximal factors consisting of perceived threats from out-group members; these threats, in turn, are predicted by distal factors such as perceived differences in group status or negative out-group contact. In the present stud3,, White and First Nation people completed measures assessing distal and proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
158
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(171 citation statements)
references
References 93 publications
13
158
0
Order By: Relevance
“…Additionally, contact quality is associated with reduced anxiety in several of the studies cited above (e.g. Corenblum & Stephan, 2001;Hewstone, 2002;Paolini, et al, 2004;, Study 3, W. G. Stephan et al, 2000, 2002. These fi ndings suggest that contact quantity, quality, and their interaction relate to reduced intergroup anxiety.…”
Section: The Infl Uence Of Contact On Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, contact quality is associated with reduced anxiety in several of the studies cited above (e.g. Corenblum & Stephan, 2001;Hewstone, 2002;Paolini, et al, 2004;, Study 3, W. G. Stephan et al, 2000, 2002. These fi ndings suggest that contact quantity, quality, and their interaction relate to reduced intergroup anxiety.…”
Section: The Infl Uence Of Contact On Anxietymentioning
confidence: 99%
“…Evidence that intergroup anxiety is related to negative attitudes toward outgroups is considerable, occurring in evaluations of African Americans (W. G. Stephan et al, 2002), Mexican immigrants in the US (W. G. Stephan, DiazLoving, & Duran, 2000), Russian immigrants in Israel (Bizman & Yinon, 2001), native Canadians (Corenblum & Stephan, 2001), prejudice toward people with cancer and AIDS (Berrenberg, Finlay, Stephan, & Stephan, 2002), reactions to Catholics and Protestants in Northern Ireland (Hewstone, 2002;Paolini, Hewstone, Cairns, & Voci, 2004), and women's evaluations of men (C. W. Stephan, Stephan, Demitrakis, Yamada, & Clason, 2000).…”
Section: Anxietymentioning
confidence: 99%
“…In his review, Gibson (2006) pointed out that perceived threat is the most important predictor of intolerance but that threat itself is an unexplained variable in nearly all studies on political tolerance. Integrated threat theory has suggested that threats mediate the impact of distal variables on attitudes toward out-groups (e.g., Corenblum & Stephan, 2001;Stephan et al, 2002). Three of these distal variables were examined in our study.…”
Section: Political Tolerance and Prejudicementioning
confidence: 99%
“…Stephan and colleagues have identified a number of antecedents of intergroup threat, such as intergroup contact, in-group identification, and status inequalities (e.g., Corenblum & Stephan, 2001;Stephan, Diaz-Loving, & POLITICAL TOLERANCE AND PREJUDICE Duran, 2000). These factors are thought to affect the level of perceived intergroup threat and, via threat, the out-group attitudes.…”
Section: Antecedents Of Intergroup Threatsmentioning
confidence: 99%
“…The concept of intergroup anxiety was introduced by Stephan and Stephan (1985) and has inspired considerable empirical attention (e.g., Britt, Boniecki, Vescio, Biernat, & Brown, 1996;Corenblum & Stephan, 2001;Islam & Hewstone, 1993;Stephan, Diaz-Loving, & Duran, 2000;Stephan et al, 1998;Stephan & Stephan, 1996). This line of theory and research suggests that intergroup anxiety toward a specific out-group (a) predicts prejudice toward this out-group (e.g., Stephan et al, 1998Stephan et al, , 2000Stephan et al, , 2002 and (b) is predicted by a lack of knowledge about the out-group and by past negative contact with this out-group (e.g., Stephan et al, 2002;Stephan & Stephan, 1989).…”
Section: Intergroup Anxietymentioning
confidence: 99%